1991
DOI: 10.1007/bf02011488
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatosis intestinalis in two infants with rotavirus gastroenteritis

Abstract: Pneumatosis intestinalis is uncommon in children other than in the premature infant with necrotizing enterocolitis (NEC). We recently observed pneumatosis intestinalis in two infants with rotavirus gastroenteritis. Both children prior to the onset of acute vomiting and diarrhea were healthy and thriving with no evidence of any underlying illness. The disease and the pneumatosis intestinalis observed in the infants presented in this paper responded well to supportive and conservative medical management. The ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…Three of the patients developed a high temperature, two abnormal LFTs (not due to GVHD) and one developed pneumatosis coli, a very rare but previously described complication of rotaviral infection. 14,15 Possible extraintestinal manifestations of rotaviral infection were recorded in four cases, with abnormal LFTs (two patients) skin rash (one patient) and encephalitis (one patient) but none of these was proven. The duration of symptoms varied between 4 days and 4 months (median duration of symptoms 15 days), with a majority of the patients being symptomatic for about 2 weeks.…”
Section: Patient Population Viral Isolation and Clinical Featuresmentioning
confidence: 99%
“…Three of the patients developed a high temperature, two abnormal LFTs (not due to GVHD) and one developed pneumatosis coli, a very rare but previously described complication of rotaviral infection. 14,15 Possible extraintestinal manifestations of rotaviral infection were recorded in four cases, with abnormal LFTs (two patients) skin rash (one patient) and encephalitis (one patient) but none of these was proven. The duration of symptoms varied between 4 days and 4 months (median duration of symptoms 15 days), with a majority of the patients being symptomatic for about 2 weeks.…”
Section: Patient Population Viral Isolation and Clinical Featuresmentioning
confidence: 99%
“…Management is directed at excluding ischemia and treating the underlying cause of mucosal injury. Although most pediatric cases outside the neonatal period are viral (particularly associated with rotavirus) [10] and can be managed expectantly, some require surgical intervention in cases of full thickness necrosis or perforation. Finally, mechanical causes of pneumatosis occur with little or no mucosal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Most reported pediatric cases of PI have occurred in patients with acute leukemia [9], acquired immunodeficiency syndrome, primary combined immunodeficiency, or post-bone marrow or renal transplantations [10][11][12], and they have often been associated with concomitant gastrointestinal infection [13]. However, Kurbegov et al [2] investigated a series of 32 patients with PI and observed that it was also present in 22% of the healthy children in their series.…”
Section: Discussionmentioning
confidence: 99%